1999
DOI: 10.7164/antibiotics.52.215
|View full text |Cite
|
Sign up to set email alerts
|

Asterriquinones Produced by Aspergillus candidus Inhibit Binding of the Grb-2 Adapter to Phosphorylated EGF Receptor Tyrosine Kinase.

Abstract: Five new asterriquinone analogs (2~4, 6, 7), together with previously identified neoasterriquinone (1) and isoasterriquinone (5), were isolated from a fermentation broth of the fungus Aspergillus candidus and purified by HSCCC(high speed counter current chromatography) followed by HPLC. The structures were determined by ID and 2D NMR and MS/MStechniques. All seven showed inhibitory activity against the binding of a recombinant protein containing the SH2 protein domain of Grb-2 to the tyrosine phosphorylated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…Diagnostic criteria of cyclic voltammetry and controlled potential coulometry accompanied by spectroscopic data (IR, 1 H NMR, 13 such as hydroxylation [17,18], dimerization [19,20], oxidative ring cleavage [21][22][23] and hydrolysis [24,25], leading to the 4a,b. The oxidation of this compound (4a,b) is easier than the oxidation of the starting molecule (1) by virtue of the presence of an electron-donating group [26].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diagnostic criteria of cyclic voltammetry and controlled potential coulometry accompanied by spectroscopic data (IR, 1 H NMR, 13 such as hydroxylation [17,18], dimerization [19,20], oxidative ring cleavage [21][22][23] and hydrolysis [24,25], leading to the 4a,b. The oxidation of this compound (4a,b) is easier than the oxidation of the starting molecule (1) by virtue of the presence of an electron-donating group [26].…”
Section: Resultsmentioning
confidence: 99%
“…At the end of electrolysis the precipitated solid was collected by filtration and washed several times with water. Products were characterized by IR, 1 H NMR, 13 C NMR, and MS. The isolated yields of 8a and 8b are shown in Scheme 1.…”
Section: Electroorganic Synthesis Of 8a and 8bmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of them are also HIV-l protease inhibitors (Fredenhagen et al, 1997), antibacterial, and toxic to insects (De Guzman et al, 1994). Other biological activities reported for these molecules include inhibition of epidermal growth factor receptor (EGF-R) tyrosine kinase (Fredenhagen et al, 1997) and inhibition of the binding of the Grb-2 adapter to phosphorylated EGFR tyrosine kinase (Alvi et al, 1999). The compound found in our screening previously had been obtained by chemical treatment of asterriquinone Bl (Arai et al, 198 1 b) but its insulin-mimetic properties were unknown.…”
Section: Lead Identification and Isolationmentioning
confidence: 99%
“…Since then several benzoquinones, such as asterriquinones [81][82][83][84] (76)(77)(78)(79)(80)(81)(82)(83)(84), isocochliodinol (85), semicochliodinols (86, 87) [89], and terphenylquinones (88)(89)(90)(91)(92), were isolated [90][91][92]. Although asterriquinones were well recognized for their antibiotic and antitumour activity [87], it took around 25 years to realize their kinase inhibitory potential [85,86,88]. The bioactivity profiling of these derivatives clearly showed that the presence of the 2,5 dihydroxy groups and which of either an indol or a phenol on 3 and 6 positions, in the benzoquinone, is necessary for bioactivity.…”
Section: Benzoquinones (Table 83)mentioning
confidence: 99%